ACCOUNTING STUDENTS’ PERCEPTION ANALYSIS ON FACTORS INFLUENCING CAREER SELECTION (A CASE STUDY IN FACULTY OF ECONOMICS AND BUSSINESS UNIVERSITY OF BRAWIJAYA) - Jauhari, Zulfifar Fritzal (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this study is to determine factors influencing career selection of the student to be public accountant or non-public accountant (accountant’s educators, internal accountant and government accountants). The influencing factors include financial rewards, professional recognition, social values, labor market considerations and intrinsic value of job. The object in this study is 46 Accounting students in Faculty of Economics and Business Brawijaya University from batch 2012 to 2016. The sample selection uses proportionated sampling based on the variety degree. The data analysis uses multiple regression tests to test independent variable and dependent variable. The results of this study indicate that there is no influenceonthe career selection from four variables which arefinancial reward, professional recognition, social values, labor market considerations, while the intrinsic score of the selection career as publicaccountant or non-public accountantis insignificant.Keywords: financial rewards, professional recognition, social values, labor market considerations, intrinsic value of job